The future of enriched, linked, open and filtered metadata : making sense of IFLA, LRM, RDA, linked data and BIBFRAME /: making sense of IFLA, LRM, RDA, linked data and BIBFRAME. (2022) - Alemu, Getaneh
No abstract available